Congenital anomalies associated with trisomy 18 or trisomy 13: A registry‐based study in 16 european countries, 2000–2011. (8th September 2015) - Springett, Anna; Wellesley, Diana; Greenlees, Ruth; Loane, Maria; Addor, Marie‐Claude; Arriola, Larraitz; Bergman, Jorieke; Cavero‐Carbonell, Clara; Csaky‐Szunyogh, Melinda; Draper, Elizabeth S.; Garne, Ester; Gatt, Miriam; et al.
Abstract : The aim of this study was to examine the prevalence of trisomies 18 and 13 in Europe and the prevalence of associated anomalies. Twenty‐five population‐based registries in 16 European countries provided data from 2000–2011. Cases included live births, fetal deaths (20+ weeks' gestation), and terminations of pregnancy for fetal anomaly (TOPFAs). The prevalence of associated anomalies was reported in live births. The prevalence of trisomy 18 and trisomy 13 were 4.8 (95%CI: 4.7–5.0) and 1.9 (95%CI: 1.8–2.0) per 10, 000 total births. Seventy three percent of cases with trisomy 18 or trisomy 13 resulted in a TOPFA. Amongst 468 live born babies with trisomy 18, 80% (76–83%) had a cardiac anomaly, 21% (17–25%) had a nervous system anomaly, 8% (6–11%) had esophageal atresia and 10% (8–13%) had an orofacial cleft. Amongst 240 Live born babies with trisomy 13, 57% (51–64%) had a cardiac anomaly, 39% (33–46%) had a nervous system anomaly, 30% (24–36%) had an eye anomaly, 44% (37–50%) had polydactyly and 45% (39–52%) had an orofacial cleft. For babies with trisomy 18 boys were less likely to have a cardiac anomaly compared with girls (OR = 0.48 (0.30–0.77) and with trisomy 13 were less likely to have a nervous system anomaly [OR = 0.46 (0.27–0.77)]. Babies with trisomy 18 or trisomy 13 do have a high proportion of associated anomalies with the distribution of anomalies being different in boys and girls. © 2015 Wiley Periodicals, Inc.